DOES BEING GREEN PAY OFF? THE ROLE OF ESG PERFORMANCE AND CARBON INTENSITY IN SHAPING GREEN BOND FINANCING AMONG ASIAN FIRMS - Lawrence, Windy; Wedari, Linda Kusumaning (Veredas do Direito, 2026)
Climate change has intensified the need for financial innovation to support sustainable transitions. Green bonds have emerged as key instruments to fund low carbon investments and promote environmental accountability. This study investigates how environmental, social, and governance (ESG) performance and carbon emission intensity affect the proportion of green bonds issued by Asian firms from 2019 to 2023. Results show that ESG score is negatively correlated with the proportion of green bonds, meaning that companies with higher sustainability credibility are less dependent on external green financing. Carbon emission intensity is positively associated with green bond proportion, indicating that firms with higher indirect emissions are more likely to use green bonds to demonstrate environmental commitment and enhance legitimacy. From sub-sample ASEAN and non-ASEAN firms highlight the role of institutional contexts in shaping sustainable finance adoption. These findings contribute by reinterpreting signaling theory and legitimacy theory within the Asian context, showing that firms with high ESG credibility refrain from costly green bond signaling due to established reputation, while firms with higher carbon emission intensity actively issue green bonds as legitimacy tools to maintain social and investor acceptance.